STUDY TO ASSESS THE PREVALENCE OF STROKE IN THE KATTANKULATHUR BLOCK OF KANCHEEPURAM DISRICT, TAMIL NADU, INDIA. - D.SURESH; K.R.JOHN (International Journal of Pharma and Bio Sciences, 2016)
Stroke is a non-communicable disease with significant socioeconomic consequence worldwide. According to a release by the World Health Organization (WHO) stroke accounts for 10.8% mortality and 3.1% of disease burden worldwide . Commonly observed deficits after stroke are loss of motor control on affected side, cognitive and perceptual dysfunction, speech and communication problems and dependent in functional activities. There are very less data available on prevalence of stroke in Tamil Nadu. Such data are important for providing rehabilitation services in community setting. The study is aimed to determine the prevalence of stroke in the kattankulathur block. This is population based descriptive survey study and the investigator carried out door to door survey with help of Stroke symptom questionnaire. In addition to door to door to survey stroke patients was collected from other resources also. All the identified patients were cross examined with CT and MRI. The results indicated that The Prevalence of stroke patient in kattankulathur block was (257/197596)* 100000 = 130 per lakh, 1 out of 769 population affected by stroke. Males are more affected then females, left hemiplegics are more than right and hypertension was predominant cause of stroke. The result from this study help us to assess the rehabilitative need and to estimate the burden on stroke in rural area. The the data was analyzed using Descriptive statistics (SPSS- version 19).The Prevalence of stroke patient in kattankulathur block was calculated using the formula Total number of stroke patients divided by total population Multiplied by 1000